Off-Label Drug Use in Acute Respiration Infection Patient at Pangandaran Hospital, Pangandaran District, West Java - Indonesia - Rahayuningsih, Nur; Priatna, Muharam; Sulistiani, Dewi A. (Pharmacology and Clinical Pharmacy Research, 2023)
Acute respiratory infections (ARIs) are infectious diseases of the upper or lower respiratory tract that cause a spectrum of illnesses from mild to severe infections. ARI is one of the leading causes of death in children in developing countries. The high incidence of ARI in children results in the use of off-label drugs. Off-label medicine is the use of drugs outside the provisions of the license relating to dose, age, route of administration, contraindications. This study aims to determine the use of off-label drugs in children with a diagnosis of ARI at Pandega Pangandaran Hospital, Pangandaran District, West Java - Indonesia. This study was an observational study with a cross sectional design and data collection was done retrospectively using Chi-square data analysis with a significance level of 0.05. Of the 84 patients who fit the inclusion criteria, there was an off-label drug use of 16.01% with the categories of off-label age (11.16%), off-label dose (4.37%), and off-label indication (0.48%) while in the category of route of administration and contraindications no off-label drug use was found. The most common type of off-label drug used was cetirizine antihistamine.  Based on the results, pharmacist’s supervision related to the risk of drug use is strongly recommended.